High-dose fish oil supplements are more effective than oily fish in altering the number and function of extracellular vesicles in healthy human subjects: a randomised, double-blind, placebo-controlled, parallel trial - Sharman, Amal; Zhou, Ruihan; Pugh, Jamie; Close, Graeme; Fisk, Helena L.; Calder, Philip C.; Yaqoob, Parveen (British journal of nutrition, 2025)
n-3 PUFA delivered by fish oil supplements alter the number and functions of circulating extracellular vesicles (EV), but consumption of oily fish does not reproduce this effect. In order to assess the effects of fish oil supplements and oily fish, at a level achievable in the diet, on EV numbers, composition and procoagulant activity in healthy human volunteers, forty-two healthy subjects were assigned to one of three treatment groups: (i) fish oil supplements plus white fish meals, (ii) control supplements plus oily fish meals or (iii) control supplements plus white fish meals for 12 weeks in a randomised, double-blind, placebo-controlled, parallel trial; circulating EV were enumerated and their procoagulant activity assessed using thrombin generation and fibrinolysis assays. Our results showed that fish oil supplements decreased circulating EV numbers and reduced EV-stimulated thrombin generation, but the consumption of oily fish at half the dose of EPA had no effect on either EV number or thrombogenic capacity. Consumption of both oily fish and fish oil supplements increased the EPA and DHA contents of EV, and the proportion of EPA in circulating EV was strongly associated with EV-stimulated thrombin generation. This study revealed that the additional 1 g/d EPA delivered in the fish oil supplements is required to decrease the numbers and thrombogenic capacity of EV, since oily fish at a level achievable in the diet had no effect. Increasing EPA intake beyond current guidelines for oily fish consumption may therefore be required for cardiovascular benefits relating to EV.